[The first shoal of salmon have been spotted before sunrise] - Garwood, Roger, 1945-; Ainslie, Trish (1999)
"The first shoal of salmon have been spotted before sunrise and the jet boat is launched over the glassy sand of the bay. Less than two hours later twenty tonne [sic] of fish will be heading for the processor in Albany."--Notes from artist.
Title devised by cataloguer based on information from acquisition file number 204/02/00071.
Photograph signed by artist on verso.
Part of the collection of photographs of the migration and catch of salmon in Cheyne Bay, Western Australia.
Also available online
Keywords: Fishing boats -- Western Australia -- Cheyne Bay -- Photographs; Tractors -- Western Australia -- Photographs; Fishers -- Western Australia -- Cheyne Bay -- Photographs; Cheyne Bay (W.A.) -- Photographs; Fishers